Edukasi Bahaya Investasi Ilegal Dan Pinjaman Online Ilegal Di Kecamatan Sangatta Kabupaten Kutai Timur - Akbar Lufi Zulfikar; Selly Swandari; Swadia Gandhi Mahardika; Priskila Angel (CV. Multi Kreasi Media, 2024)
The success of the implementation of socialization activities about online loans in Sangatta District, East Kutai Regency is due to supporting factors, including: 1. The great desire of the community to know and understand the material on the definition of personal data protection, personal data protection regulations; 2. There is support from leaders in Sangatta District, East Kutai Regency. In the implementation of this activity as a whole, it can reduce inhibiting factors, but these inhibiting factors also arise, including some participants who are not serious because they are not used to sitting for hours so that some shout and talk to each other with other participants, some enter and leave the room without permission.